Answer:
See below
Step-by-step explanation:
<u>Parent function:</u>
<u>Transformed function:</u>
- y = 4(3)⁻²ˣ⁺⁸ + 6, (note. I see this as 8, sorry if different but it doesn't make any change to transformation method)
<u>Transformations to be applied:</u>
- f(x) → f(-x) reflection over y-axis
- f(-x) → f(-2x) stretch horizontally by a factor of 2
- f(-2x) → f(-2x + 8) translate 8 units right
- f(-2x + 8) → 4f(-2x + 8) stretch vertically by a factor of 4
- 4f(-2x + 8) → 4f(-2x + 8) + 6 translate 6 units up
790 i think sorry if it's wrong :/
Answer:
x = 4
Step-by-step explanation:
<u>Step 1: Set both parts equal to 0</u>
x - 4 = 0 and x - 4 = 0
<u>Step 2: Solve for x by adding 4 to both sides</u>
x - 4 + 4 = 0 + 4 and x - 4 + 4 = 0 + 4
x = 4 and x = 4
Answer: x = 4
Answer:
Midpoint is
.
Step-by-step explanation:
Given points are
and 
Midpoint of points
and
is 
Therefore, 



Answer:
Its D
Step-by-step explanation: